A systematic review of the cost-effectiveness of maternity models of care - Elizabeth Martin; Bassel Ayoub; Yvette D. Miller (BMC, 2023)
Abstract Objectives In this systematic review, we aimed to identify the full extent of cost-effectiveness evidence available for evaluating alternative Maternity Models of Care (MMC) and to summarize findings narratively. Methods Articles that included a decision tree or state-based (Markov) model to explore the cost-effectiveness of an MMC, and at least one comparator MMC, were identified from a systematic literature review. The MEDLINE, Embase, Web of Science, CINAHL and Google Scholar databases were searched for papers published in English, Arabic, and French. A narrative synthesis was conducted to analyse results. Results Three studies were included; all using cost-effectiveness decision tree models with data sourced from a combination of trials, databases, and the literature. Study quality was fair to poor. Each study compared midwife-led or doula-assisted care to obstetrician- or physician-led care. The findings from these studies indicate that midwife and doula led MMCs may provide value. Conclusion The findings of these studies indicate weak evidence that midwife and doula models of care may be a cost-effective or cost-saving alternative to standard care. However, the poor quality of evidence, lack of standardised MMC classifications, and the dearth of research conducted in this area are barriers to conclusive evaluation and highlight the need for more research incorporating appropriate models and population diversity.